Heterostructures between a tin-based intermetallic compound and a layered semiconductor for gas sensing. Issue 45 (10th May 2021) - Bao, Jusheng; Zeng, Shaoyu; Dai, Jie; Wang, Xiaoshan; Liu, Qiang; Li, Hai; Huang, Xiao; Huang, Wei
Abstract : Pt3 Sn nanoparticles are in situ deposited on SnS2 nanoplates to form heterostructures, which show promise as a selective NO2 sensing material at room temperature. Abstract : SnS2 nanoplates are used as sacrificial templates to facilitate the in situ growth of intermetallic compound Pt3 Sn nanoparticles. The Pt3 Sn/SnS2 heterostructures show promise for selective NO2 sensing due to the favored gas adsorption and gas–solid charge transfer on Pt3 Sn, combined with the optimized film conductance and formation of ohmic-type Pt3 Sn/SnS2 heterointerfaces.